(untitled) (Bangladesh Pharmaceutical Journal, 2025)
This research project aims to explore the medicinal properties of Staurogyne zeylanica Kuntze, a relatively underexplored plant from the Acanthaceae family. Recent studies suggest that this plant may have a diverse array of therapeutic properties. Methanol extracts of S. zeylanica Kuntze demonstrated significant analgesic effects (59.05 %) comparable to morphine, indicating its potential as a pain-relief agent. Although the extracts exhibited hyperglycemic effects, they did not result in significant reductions in blood glucose levels. Central nervous system (CNS) tests suggested mild depressant effects, pointing to possible applications in treating conditions like depression. Additionally, higher doses of the extracts showed promising anti-diarrheal activity (74.29%), significantly reducing diarrhea. The aqueous extract also exhibited notable inhibition of haemolysis (60.5%) in heat-induced condition, suggesting potential protective effects against oxidative stress or cellular damage and low thrombolytic activity (12.41%). These findings underscore the pharmacological potential of S. zeylanica Kuntze and highlight the need for further research, including clinical trials, to fully validate and expand its therapeutic applications. Bangladesh Pharmaceutical Journal 28(1): 28-36, 2025 (January)